Situs-Situs Mitologis di Gunung Kelud untuk Konservasi Warisan Budaya - Fandana Syahwa Audyva; A Zahid (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2026)
This study aims to examine mythological sites around Mount Kelud as living cultural heritage and explore how they are understood in relation to myths, beliefs, and community cultural practices. Previous research has discussed Mount Kelud through the lenses of tradition, ritual, mythology, and cultural history, yet no study has specifically positioned its mythological sites within the framework of cultural heritage conservation. This research employed a qualitative descriptive method with data collected through in-depth interviews, field observation, and documentation, involving informants selected through purposive sampling. Findings reveal that mythological sites including the crater, punden, sacred springs, and ancient trees function as connectors between collective memory and cultural identity. Local narratives such as the Lembu Suro, Dewi Kilisuci and Mahesa Suro, Dewi Sekartaji myths continue to shape beliefs and taboos. Rituals including Larung Sesaji, Nyiram Tuwuh, and slametan demonstrate that these sites remain functionally significant in social, spiritual, and economic life, constituting a form of living cultural heritage that must be preserved.